2021
DOI: 10.1038/s41541-021-00351-2
|View full text |Cite
|
Sign up to set email alerts
|

Links between fecal microbiota and the response to vaccination against influenza A virus in pigs

Abstract: This study describes the associations between fecal microbiota and vaccine response variability in pigs, using 98 piglets vaccinated against the influenza A virus at 28 days of age (D28) with a booster at D49. Immune response to the vaccine is measured at D49, D56, D63, and D146 by serum levels of IAV-specific IgG and assays of hemagglutination inhibition (HAI). Analysis of the pre-vaccination microbiota characterized by 16S rRNA gene sequencing of fecal DNA reveals a higher vaccine response in piglets with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 78 publications
1
24
1
Order By: Relevance
“…Understanding IAV infection and the role of the microbiota in this large natural animal model has enormous potential for unraveling the causal links between changes in the microbiota and immunity to infection or immunization. Recently, a study showed the association between the presence of genus Prevotella and Muribaculaceae families in the feces and a stronger antibody response to immunization against IAV in pigs [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding IAV infection and the role of the microbiota in this large natural animal model has enormous potential for unraveling the causal links between changes in the microbiota and immunity to infection or immunization. Recently, a study showed the association between the presence of genus Prevotella and Muribaculaceae families in the feces and a stronger antibody response to immunization against IAV in pigs [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Functional interactions between the gut microbiome and the vaccination response were first described in humans and mice [ 20 , 21 , 22 , 23 ]. In piglets, the composition of the microbiota before vaccination was predictive of the quantitative response after influenza A virus vaccination [ 24 ]. In bovines, a significant association was observed between bacterial communities of the bovine fecal microbiota and the immune response after parenteral vaccination against E. coli O157:H7 [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination against specific pathogens has been an extensive method to control infectious diseases for a long time now. Primary function of all vaccines is the stimulation of the immune system against specific antigens, while one of the main tasks of the microbiota is to contribute to the maturation of the immune system 17 20 . Thus, the influence of the microbiota on the vaccine response has been more studied than the effect that the vaccines may have in the host microbiota and, in particular, in the microbiota of the progeny 16 , 21 .…”
Section: Discussionmentioning
confidence: 99%